Compatibility of Pupil Size Measured with Nidek ARK-1a Table Top Autorefractometer and Plusoptix A12C Photoscreener. Issue 4 (2nd October 2021) - Guler Alis, Meryem; Alis, Abdulkadir
ABSTRACT: Aim : To evaluate the differences in pupil size measured with and without cycloplegia by a table top autorefractometer, ARK-1a Auto Ref/Keratometer, Nidek, Japan, 2014 release, compared to handheld photoscreener, Plusoptix A12C, software 6.1.12, under monocular and binocular conditions. Materials and Methods: In the study, 100 eyes of 100 patients ages 18–55 years were included. The patients' pupil sizes were measured with a table top autorefractometer, Nidek ARK 1a without cycloplegia, and then the pupils were remeasured under monocular and binocular conditions with a photoscreener, Plusoptix A12C, respectively. After that the measurements with cycloplegia were repeated in the same order. The values obtained with both devices were compared. Results: In the measurement results without cycloplegia, the pupil size measured by Nidek ARK 1a was found to be significantly different than that measured by Plusoptix A12C under both monocular and binocular conditions. Pupil size measured with Plusoptix A12C under monocular conditions was also different than pupil diameter measured under binocular conditions. In the measurements with cycloplegia, it was observed that the pupil size measured with Plusoptix A12C under monocular and binocular conditions was not different from the diameter measured with Nidek ARK 1a. Conclusion: Pupil sizes measured with Nidek ARK 1a and Plusoptix A12C in monocular and binocular conditions without cycloplegia are different, but measurements with cycloplegia are similar. We believe that pupil size measurement with Plusoptix A12C under binocular conditions without cycloplegia will be more appropriate when necessary as a screening device in clinical settings.